2016
DOI: 10.5603/ep.2016.0004
|View full text |Cite
|
Sign up to set email alerts
|

Analiza znaczenia klinicznego niejednoznacznych wyników biopsji tarczycy ze szczególnym uwzględnieniem kategorii ZPBN na podstawie 5 lat stosowania nowej klasyfikacji rozpoznań cytologicznych

Abstract: Introduction: The diagnostic category of follicular lesion of undetermined significance (FLUS) was intended to allow selection of cases with low risk of malignancy from all smears with indeterminate, suspicious cytology (ISC), which can potentially take advantage from repeat fine-needle aspiration (rFNA). Aim of the study was a comparison of the risk of malignancy related to FLUS nodules and other nodules with ISC: suspected follicular neoplasm (SFN) and suspected malignancy (SM), as well as analysis of the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Such a design has both advantages (certainty of the correct diagnosis of benign and malignant lesions) and disadvantages (a bias introduced by the additional selection of nodules). But in our material the difference in the risk of malignancy in FLUS nodules, as determined by histopathological examination and cytological follow-up, is not big (<3%) [25]. Our previous study also showed that there were no differences in the ultrasound image of FLUS nodules in the patients treated surgically and conservatively.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Such a design has both advantages (certainty of the correct diagnosis of benign and malignant lesions) and disadvantages (a bias introduced by the additional selection of nodules). But in our material the difference in the risk of malignancy in FLUS nodules, as determined by histopathological examination and cytological follow-up, is not big (<3%) [25]. Our previous study also showed that there were no differences in the ultrasound image of FLUS nodules in the patients treated surgically and conservatively.…”
Section: Discussionmentioning
confidence: 46%
“…Our previous study also showed that there were no differences in the ultrasound image of FLUS nodules in the patients treated surgically and conservatively. Patients treated surgically were younger and had larger nodules [25]. A disadvantage of our study is the relatively low number of cancers in the FL group, but it reflects the frequency of cancers in this cytological category in our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of category IV the risk of malignancy in a nodule is usually over 15% and a surgical treatment is recommended [1]. But in areas of iodine deficiency or in post-endemic areas that risk may be lower (due to non-neoplastic hyperplastic follicular nodules outnumbering follicular neoplasms), and then the decision on the surgical treatment becomes less obvious [3,4]. The risk of malignancy of category III is more diverse and it ranges from 5% to as much as 50% [5][6][7][8][9] among various centres.…”
Section: Introductionmentioning
confidence: 99%